New proof of the theorem of existence and uniqueness of geometric fractional Brownian motionequation - Alhagyan, Mohammed; Misiran, Masnita; Omar, Zurni (Research India Publications, 2016)
This paper provides a proof of existence and uniqueness theorem for the geometric fractional Brownian motion equation.The proof uses an approximation approach in addition to some inequalities.